PENGEMBANGAN MEDIA ALPHABOOK BERTEMA HEWAN PADA MATERI KETERAMPILAN MEMBACA UPT SD NEGERI 39 GRESIK - Ainur Rosyidah; Nanang Khoirul Umam; Nataria Wahyuning Subayani (Nusantara Hasana Berdikari, 2022)
This study aims to develop learning media and to determine the validity and response of students to the use of Alphabook media on reading skills material at UPT SD Negeri 39 Gresik. The hope of this development research can facilitate the ease of pronouncing sentences in grade II elementary school. This type of research is development research using the ADDIE model adopted from the Robert Marribe Branch which has 5 stages, namely: the analysis stage (analysis), the design stage (design), development (development), the implementation stage (implementation) and the evaluation stage (evaluation). The results of the research that have been carried out show that the development of Animal-themed Alphabook media on the Reading Skills Material of UPT SD Negeri 39 Gresik meets the indicators, namely: a) the validation results from 2 media expert validators obtain an average percentage value of 89.2% which is included in the very criteria. valid, b) the validation results from 2 material expert validators obtained an average percentage value of 94% which was included in the very valid criteria, and c) the results of the 19 student responses obtained a percentage value of 96.8% which indicated the media was included in the very good category. Based on this description, the learning media and materials contained in the media developed by researchers can be used in the learning process.